2001
DOI: 10.2337/diabetes.50.8.1857
|View full text |Cite
|
Sign up to set email alerts
|

Menopause in Type 1 Diabetic Women

Abstract: Women with type 1 diabetes have a delayed menarche and a greater prevalence of menstrual disorders than women without diabetes. However, little is known about the menopause transition among type 1 diabetic women. The Familial Autoimmune and Diabetes (FAD) Study recruited both adult individuals who were identified from the Children's Hospital of Pittsburgh Type 1 Diabetes Registry for the years 1950 -1964 and their family members. Unrelated nondiabetic control probands and their relatives were also evaluated. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
2
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 62 publications
2
89
2
6
Order By: Relevance
“…The expected effect on ovarian cancer risk would be too small, however, to explain our findings. It is unclear whether parity differs between women with type I diabetes and other women (Dorman et al, 2001), but the differences would need to be very large to explain our results. We know of no evidence on oophorectomy prevalence in women with diabetes.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The expected effect on ovarian cancer risk would be too small, however, to explain our findings. It is unclear whether parity differs between women with type I diabetes and other women (Dorman et al, 2001), but the differences would need to be very large to explain our results. We know of no evidence on oophorectomy prevalence in women with diabetes.…”
Section: Discussionmentioning
confidence: 75%
“…It is a limitation that we do not have individual data on menstrual or reproductive factors in our cohort, but menstrual factors in studies of women with type I diabetes have been in a direction to give diminished, not raised, risk of ovarian cancer: episodes of amenorrhoea are more frequent in women with insulin-dependent diabetes than in women in general (Kjaer et al, 1992); menarche is delayed in women with diabetes incident under age 10 years (Kjaer et al, 1992); and limited evidence suggests that menopause is considerably younger in women with childhood onset type I diabetes (Dorman et al, 2001). Oral contraceptive (OC) use is protective against ovarian cancer , and there is evidence that OC use is less common in patients with diabetes (Dorman et al, 2001), because of potential side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population of interest is postmenopausal women because although natural menopause represents a normal aspect of aging, it is also associated with increased risk for a variety of diseases such as osteoporosis (Eichner et al, 2003), type 1 diabetes (Dorman et al, 2001), cardiovascular diseases (Gorodeski, 1994, and breast cancer (Edwards et al, 2002). Because numerous studies use data from self-reported questionnaires to assess the association between diet and disease in postmenopausal women it is important to understand the magnitude of dietary intake misreporting in this population.…”
Section: Introductionmentioning
confidence: 99%
“…While it has not been definitively proven, some recent studies suggest that T1D patients may experience an earlier onset of menopause compared to the general population [15]. Early menopause means ovarian failure occurs earlier, decreasing the number of years available to have children.…”
Section: Reproductive Life Planmentioning
confidence: 99%